The Role of Umbilical Cord-Derived Mesenchymal Stem Cells (UC-MSC) in Rheumatoid Arthritis: A Literature Review and Bibliographic Study - Bastian Bastian; Radiyati Umi Partan; Krisna Murti; Ayeshah Augusta Rosdah (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Umbilical Cord-derived Mesenchymal Stem Cells (UC-MSCs) are promising candidates for innovative therapy in rheumatoid arthritis (RA) due to their immunomodulatory and regenerative properties. RA is a chronic autoimmune disease characterized by persistent synovial inflammation, progressive joint destruction, and immune dysregulation involving T cells, B cells, and pro-inflammatory cytokines such as TNF-α, IL-1β, and IL-6. This study aims to analyze the research development and therapeutic potential of UC-MSCs in RA through a bibliometric approach and literature review. Data were collected from PubMed, Dimensions, ScienceDirect, and Google Scholar databases covering the period 2016–2025 using relevant keywords related to UC-MSC and RA. Bibliometric analysis was performed using VOSviewer to map publication trends, scientific collaborations, and research topic clusters, while the literature review was used to evaluate the underlying mechanisms and therapeutic effectiveness. The results indicate a significant increase in UC-MSC research in recent years, with a primary focus on immunomodulatory mechanisms and clinical applications. Biologically, UC-MSCs have been shown to suppress synovial hyperplasia, inhibit pro-inflammatory cytokine production, and increase regulatory T cell (Treg/FOXP3) populations, thereby promoting immune tolerance and tissue repair. Preclinical and clinical studies have reported reductions in disease activity scores and improvements in joint function. However, the limited number of large-scale clinical trials and insufficient exploration of specific molecular mechanisms remain major challenges. Therefore, further studies are required to optimize the clinical application of UC-MSCs as a regenerative and immunomodulatory therapy for RA.